2019
DOI: 10.1093/brain/awz362
|View full text |Cite|
|
Sign up to set email alerts
|

The role of haematological traits in risk of ischaemic stroke and its subtypes

Abstract: Thrombosis and platelet activation play a central role in stroke pathogenesis, and antiplatelet and anticoagulant therapies are central to stroke prevention. However, whether haematological traits contribute equally to all ischaemic stroke subtypes is uncertain. Furthermore, identification of associations with new traits may offer novel treatment opportunities. The aim of this research was to ascertain causal relationships between a wide range of haematological traits and ischaemic stroke and its subtypes. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 69 publications
(78 reference statements)
2
26
0
Order By: Relevance
“…Fibrinogen (Fib), as a thromboplastic and inflammatory marker, facilitates blood viscosity, platelet aggregation, fibrin cross-linking, and plays a pivotal role in the progression of atherosclerosis [1,2]. Previous studies showed that Fib was not only an indicator of subclinical cardiovascular diseases, such as coronary artery calcification and intima-media thickness of the carotid artery [3,4], but was also independently associated with the development of coronary artery disease (CAD), hypertension, stroke, as well as adverse cardiovascular events [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Fibrinogen (Fib), as a thromboplastic and inflammatory marker, facilitates blood viscosity, platelet aggregation, fibrin cross-linking, and plays a pivotal role in the progression of atherosclerosis [1,2]. Previous studies showed that Fib was not only an indicator of subclinical cardiovascular diseases, such as coronary artery calcification and intima-media thickness of the carotid artery [3,4], but was also independently associated with the development of coronary artery disease (CAD), hypertension, stroke, as well as adverse cardiovascular events [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Previous studies have shown that fibrinogen was not only independently associated with the development of CAD, hypertension and stroke, but also an independent predictor of long-term prognosis in patients after PCI. [12][13][14] More recently, it has been reported that the D-dimer to fibrinogen ratio (DFR) is a novel predictor for the outcomes of pulmonary thromboembolism (PTE), ischemic stroke and gastrointestinal stromal tumors (GISTs). [15][16][17] However, the relationship between the DFR and prognosis in CAD patients after PCI has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…33 Interestingly, reduced FVIII activity was associated with ischemic stroke risk, and specifically the cardioembolic and large artery atherosclerosis subtypes (the latter only among the European population). 33 Our study was not powered to investigate stratum-specific effects across the stroke subtypes, but this area warrants future research also in the context of secondary event prevention.…”
Section: Re Sultsmentioning
confidence: 99%